The correlates of HIV testing and impacts on sexual behavior: evidence from a life history study of young people in Kisumu, Kenya - Izugbara Chimaraoke O; Luke Nancy; Kabiru Caroline W; Zulu Eliya M (BMC, 2010)
Abstract Background HIV counseling and testing is considered an important component of HIV prevention and treatment. This paper examines the characteristics of young males and females at the time of first reported HIV test, including the influence of recent sexual partnerships, and investigates how HIV testing and the cumulative number of tests are associated with sexual behaviors within six months of testing. Methods The study uses data from a random sample of youth aged 18-24 years living in Kisumu, Kenya, who were interviewed using a 10-year retrospective life history calendar. Cox regression models were used to examine the correlates of the timing of first HIV test. Variance-correction models for unordered repeated events were employed to examine whether having an HIV test in the previous six months and the cumulative number of tests predict unsafe sexual practices in a given month. Results Sixty-four percent of females and 55% of males reported at least one HIV test in the last 10 years and 40% of females were pregnant the month of first test. Significant correlates of first HIV test included marital aspirations among non-pregnant females, unprotected sex in the previous six months among pregnant females, and concurrency in the previous six months among males. Having a recent HIV test was associated with a decreased likelihood of unprotected sex among ever-pregnant females, an increased likelihood of unprotected sex and "risky" sexual partnerships among never-pregnant females, and an increased likelihood of concurrency among males. Repeated HIV testing was associated with a lower likelihood of concurrency among males and involvement in "risky" sexual partnerships among males and never-pregnant females. Conclusions The high rate of pregnancy at first test suggests that promotion of HIV testing as part of prevention of mother-to-child transmission is gaining success. Further research is warranted to examine how and why behavior change is influenced by client- versus provider-initiated testing. The influence of different sexual partnership variables for males and females suggests that interventions to assess risk and promote testing should be gender- and relationship-specific. The findings also suggest that encouraging repeat or routine testing could potentially increase the uptake of safer sexual behaviors.